2010
DOI: 10.1055/s-0030-1249020
|View full text |Cite
|
Sign up to set email alerts
|

Very High Frequency of the Polymorphism for the Insulin Receptor Substrate 1 (IRS-1) at Codon 972 (Glycine972Arginine) in Southern Italian Women with Polycystic Ovary Syndrome

Abstract: A major component of the polycystic ovary syndrome (PCOS) is the insulin resistance. Only a few studies have evaluated the IRS-1 polymorphism at codon 972, sometimes in the absence of a control group, and with great variability in frequency (0-23% in PCOS vs. 0-17% in controls), and with no unequivocal relationships between the polymorphism and clinical or biochemical indexes. The aim of the work was to evaluate the frequency of the IRS-1 polymorphism at codon 972 in PCOS, and correlate it to clinical and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Ioannidis et al published a meta-analysis on IRS-1 Gly972Arg polymorphism, and got conclusions that the Arg972 allele was associated with an increased risk for developing PCOS [16]. But recent four researches in the association between IRS-1 Gly972Arg polymorphism and PCOS still had different conclusions [19][20][21][22]. We excluded in Asia population were limited, subgroup analyses were not considered in our research.…”
Section: Gly972arg Polymorphismmentioning
confidence: 88%
See 1 more Smart Citation
“…Ioannidis et al published a meta-analysis on IRS-1 Gly972Arg polymorphism, and got conclusions that the Arg972 allele was associated with an increased risk for developing PCOS [16]. But recent four researches in the association between IRS-1 Gly972Arg polymorphism and PCOS still had different conclusions [19][20][21][22]. We excluded in Asia population were limited, subgroup analyses were not considered in our research.…”
Section: Gly972arg Polymorphismmentioning
confidence: 88%
“…After review, a total of 16 published articles reported on the relationship between these two IRS gene polymorphisms and PCOS met the inclusion criteria [12][13][14][15][19][20][21][22][23][24][25][26][27][28][29], 15/16 were about the Gly972Arg polymorphism, 5/16 were about the Gly1057Asp polymorphism. These articles were published between 2001 and 2011.…”
Section: Eligibility Of Studiesmentioning
confidence: 99%
“…In addition, polymorphism studies are mostly dependent on ethnicity and variability within different geographic regions which could affect study results. Recently a study was done to find out the prevalence of different codons of IRS-1 in PCOS patients in different European ethnicities with different results [15,16]. The present study was therefore undertaken to investigate the frequency of IRS1Gly972Arg and IRS2 Gly1057Asp polymorphisms and to compare the prevalence of these two polymorphisms in PCOS patients and non-diabetic healthy women in Iranian subjects.…”
Section: Introductionmentioning
confidence: 95%
“…However, some articles reported associations of Gly972Arg and Gly1057Asp polymorphisms with PCOS, but the results of these studies were conflicting. Recent four researches in the association between IRS-1 Gly972Arg polymorphism and PCOS still had different conclusions [38][39][40][41]. Very recent meta-analysis by Ruan Y in 2012 concluded that IRS-1 Gly972Arg polymorphism is associated with PCOS, and this variation might be considered as a risk factor for PCOS further this study also concluded that no significant association was detected between IRS-2 Gly1057Asp polymorphism and PCOS [12].…”
Section: Irs1 -Gly972arg Polymorphismmentioning
confidence: 81%